The Usage of Home Water Filtration System in Malaysia - Abd Rahim, Nur Shahirah (International Journal of Integrated Engineering, 2020)
Installation of a water filter system for household use has become a necessity for Malaysians to get safe drinking water quality. Various types of machinery products of water filters have entered the Malaysian market with certain quality assurance. In the present, there were no guidelines for the water filter system in Malaysia that can prove water quality assurance given by the provider. The aim in this study is to produce a good reference based on the factor affecting the user choosing a water filter system. The method that was used is the collection of data from the questionnaire and survey of feedback from consumers. This result can determine the pattern and selection factor of a water filter machine product. The major factor in the selection of water purifier machines is the price offered and the main information about the product is obtained through the advice of friends and neighbours. The second aim of this study was conducted to determine the quality of the water filter before and after through a water filter system. The results of water quality tests before and after through water filter system showed three forms of concentration changes in chemical water quality parameters were tested. First forms of concentration, there was a high percentage removal rate that exceeds 75% in all types of water filter brands. Second, the result of the water quality test for tap water and after filtering water sample shows no significant difference for the concentration parameters before and after passing through a water filter system. Third, there was an increased in the concentration of water after through water filter system. The results of chemical water quality test for three brands which have twelve parameters was given good performance on Brand A (Model 1). However, the water quality before and after passing through a water filter system still meets drinking water standards of the Ministry of Health. The results of this study can be used as a reference source for Safety Division and Food Quality, Ministry of Health Malaysia in developing water filter system guidelines for household use.